PEMBUATAN DAN KARAKTERISASI ELEKTRODA SELEKTIF ION (ESI) TIMBAL (II) TIPE KAWAT TERLAPIS BERBASIS PIROPILIT - Daninda, Mahani; Fardiyah, Qonitah; Sabarudin, Akhmad (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
ABSTRACT Pyrophyllite as an inorganic material having an active site that can serve as an ion exchanger, so that potentially to be used as ionophore ion selective membrane. Ion Selective Electrode (ISE) lead (II)-based on pyrophyllite as an ionophore, Polyvinylchloride (PVC) as the matrix polymer, activated carbon and dioktilftalat (DOP) as a plasticizer in tetrahydrofuran solven has been developed. Variables of this research consist of immertion time doing at 10, 20, 30, 40, 50, 60, 70, 80 minutes and composition of the membrane. Basic characterization of ion ISE Lead (II) coated wire based on pyrophyllite were examined Nernst Factor, limit of detection, linear concentration range, response time, and life time. The results of research showed that, the optimum immertion time to 50 minutes, with the optimum membrane composition consist of Pyrophylite : PVC : activated carbon : DOP is 49 : 16 : 3 : 32 (% b/b). Characterization of Lead (II)-based coated wire type pyrophyllite produced include: linear concentration range of lead 10-5 - 10-1 M at a price of 29.33 Nernst Factor mV/decade of concentration. The resulting detection limit is 8.054 x 10-6 M or equal to 1,669 ppm of lead, the resulting response time of 30 seconds and a life time of 45 days. Keywords : coated wire type, Ion Selective Electrode (ISE), lead, pyrophyllite